Perawatan dan Perbaikan Dalam Upaya Peremajaan Kapal Batam Marine Ambulance - Fauzun Atabiq; Irwanto Zarma Putra; Muhammad Syafei Gozali; Arif Wahyu Budiarto; Muhammad Nurhidayat; Kartika Kartika; Ari Wibowo; Nugroho Pratomo Ariyanto; Nurul Laili Arifin; James Siregar; Wowo Rossbandrio; Muhammad Andi Nova; Rizky Pratama Hudhajanto; Annisa Fyona; Yogantara Yogantara; Meida Perwira Antartika; Rahman Hakim (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2022)
Marine ambulance, as medically equipped vehicle which tranports patient to referral facilites, is very important in Batam archipelago. Routine maintenance activities is conducted to ensure all systems function properly. The maintenance includes maintenance of ship mechanics and ship engines, electrical systems, and hull cleaning. Maintenance standard operating procedure (SOP) is composed to help ship crew conducting ship maintenance. The maintenance activity repairs system problems successfully and appreciated by ship crew, LAZ Batam, and Awal Bros Hospital as service provider; and community who benefited by the service. Healthcare service operates well although some respondents think there is lack of equipments. Safety equipment and medical equipment are not enough for 13% and 20% respondents, respectively. However, all respondent think that the maintenance activity has repaired ship system and ensure ship to operate properly, and deliver healthcare service well.